PERENCANAAN STRATEGIS SISTEM INFORMASI MENGGUNAKAN METODE WARD AND PEPPARD DI STAI ATTANWIR - Makhabbatillah, Vina (Universitas Methodist Indonesia, 2024)
This research focuses on strategic planning of information systems (IS) at STAI Attanwir by applying the Ward and Peppard method. The main objective of this research is to increase the effectiveness of data management, management efficiency, and organizational competitiveness through an IS strategy that is integrated with business objectives. Through SWOT, PEST and Porter's Five Forces analysis, this research identifies the strengths, weaknesses, opportunities and threats faced by STAI Attanwir in the context of the internal and external business environment. The results of this analysis are used to develop an IS/IT strategy that includes application portfolio development, information architecture and comprehensive IT management. In addition, this research emphasizes the importance of strong technological infrastructure and information security in supporting institutional operations. By implementing the right IS/IT strategy, it is hoped that STAI Attanwir can increase its efficiency, transparency and competitiveness through the effective and relevant use of information technology